1H NMR spectroscopy and multivariate analysis as possible tool to assess cultivars, from specific geographical areas, in EVOOs. Issue 9 (16th December 2015) - Girelli, Chiara Roberta; Del Coco, Laura; Fanizzi, Francesco Paolo
Abstract : In this work, we tested a NMR‐based MVA method to assess the authenticity of EVOOs cultivar (from specific origin) declaration by using a total of over a 100 samples coming from different selected areas of Southern Italian Regions (Apulia and Calabria). We built a reference model, by performing unsupervised PCA and supervised PLS‐DA, OPLS‐DA analyses on the 1 HNMR spectra of a 40 monovarietal EVOOs training set. These included 10 Coratina (the most popular Apulian cultivar) together with 10 Picholine, 10 Ogliarola Barese, and 10 Carolea samples (the most common Coratina bitterness smoothers cultivars used in Coratina‐based blends). The training set originated PLS‐DA reference model was profitably used to assess the class membership for a series of declared monocultivar EVOO samples and to obtain a clear indication for the composition of Coratina‐based blends. By using the same reference model we analyzed in blind a test set formed by 40 unknown samples coming from the same areas and we predicted their class or blend composition affinity (later confirmed by suppliers as Coratina‐ or Coratina‐based blends). This proposed method could be a simple and quick tool to assess, also for trading purpose, the cultivar (from given geographical areas) declaration of labeled EVOOs. Practical applications: EVOO is one of the most important element of the Mediterranean diet with its numerous health benefits due to the chemical composition (unsaturated fatty acids and minor components). For this high commercial value in the recent years, EVOO has been processed to adulteration process with seeds oils, refined pomace, and esterified oils with serious damage to its quality. In order to guarantee the quality of this important product, EU Regulation 182 of March 6, 2009, stated the obligatory labeling of EVOO samples with the geographical production area for all European countries. Surprisingly, this regulation lacks of an official methodology to assess the origin and the cultivar of EVOOs. A quick and reproducible method to check the label declaration of commercial EVOOs could be attractive for industry and ensure transparency for consumer choices. Work flow chart illustrating the procedures sequence to assess cultivars, from specific geographical areas, in EVOOs. A reference model is built and its prediction capability is tested with monovarietal and blend commercial extra virgin olive oil samples. Abstract : Work flow chart illustrating the procedures sequence to assess cultivars, from specific geographical areas, in EVOOs. A reference model is built and its prediction capability is tested with monovarietal and blend commercial extra virgin olive oil samples.